Applications of Social Network Analysis in Human Resource Development - R. Venkattakumar; P.Manikandan (Journal of Agricultural Extension Management, 2025)
Social network analysis (SNA) is a technique that focuses on identifying and comparing relationships within and between individuals, groups and systems in order to model the real world interactions at the heart of organizational knowledge and learning processes. SNA promises to add significantly to theory building in the field of Human Resource Development (HRD) by providing a methodological approach for improving empirical rigor of conducting research in organizational development, organizational learning, leadership development, training and development. Thus, SNA can play an important role in moving HRD forward. An attempt has been made here to project SNA as a methodology to approach, deal, analyze, plan issues related to HRD. Since HRD forms a vital component of extension management, SNA methodology gains strategic significance.